A review of copper cyanide recovery technologies for the cyanidation of copper containing gold ores - Dai, X.; Simons, Andrew; Breuer, P. (Elsevier, 2012)
Many gold producers are today processing gold ores containing significant amount of cyanide soluble copper. Typically, cyanide destruction is used to prevent the discharge of copper cyanide into tailings storage facilities. This imposes a significant financial cost to producers from the additional cyanide used to solubilise the copper and the cost of cyanide destruction reagents. Therefore, the recovery of copper as a valuable by-product and the recycle of cyanide to the leach circuit have the potential for significant economic and environmental benefits. This includes enabling the treatment of gold ores with even higher soluble copper. Over the years, a variety of processes have been developed or proposed to recover the copper and/or cyanide including acidification based technologies such as AVR and SART, direct electrowinning, activated carbon, ion exchange resins, solvent extraction, polychelating polymers, and membrane technologies. In this paper, these processes are critically reviewed and compared, with particular focus on the advantages and limitations, and the separation of copper from cyanide. Ultimately, there is no universal process solution and the choice is highly dependent on the nature of the stream to be treated and integration with the whole processing plant.